The choice of the optimal braking force on the wheelset, taking into account the imper-fection of antiskid devices - I. A. Zharov; S. B. Kurtsev; A. A. Makas (Вестник Научно-исследовательского института железнодорожного транспорта)
As it is known, the growth of the braking force leads to a reduction in the braking distances with sufficient force of adhesion and its increase - if insufficient. This allows to set the task of choosing the optimal braking force on the wheel pair by the criterion of minimizing losses due to the increase in braking distances.To formulate the optimization problem, it is necessary to relate the gain from the reduction of the braking distances with good adhesion and the loss from its increase with poor adhesion due to the imperfect operation of the antiskid devices. To do this, author introduces the concept of ”loss function”, which includes internal and external damages during braking, and also uses the function of probability density q () of the potential coefficient between the wheel and the rail during braking.The proposed model is rather simplistic, therefore, it is reasonable to consider the conclusions from its analysis as qualitative, and for additional quantitative estimates additional sources of information should be involved. So, for example, in this case, similar quantitative conclusions can be obtained from the following assumptions.On the one hand, according to the results of numerous tests carried out in 2008 - 2016, values close to 0.3 (mainly at low speeds and using regenerative braking) are already achieved on wheel pairs of motor carriages of modern electric trains. On the other hand, the parameters of modern anti-skid devices are such that the values of greater than 0.2 can lead to wheel pair damage due to entry into the skid. In addition, exceeding the deceleration value of 2.5 m / s2 (coefficient of traction of the train above 0.25) can lead to disruption of the longitudinal stability of the track to shift.In general, the analysis of simulation results shows that the choice of the upper limit for the coefficient of adhesion = 0.3, laid down by the state standard for electric trains, is sufficiently substantiated. Secondly, the coefficients of efficiency of the using coupling of modern anti-skid devices make it reasonable to set the value of on the axis to at least 0.2 during an emergency braking.